A New ZVT Snubber Cell for PWM-PFC Boost Converter - Bodur, Haci; Yildirmaz, Suat (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
In this paper, a new zero-voltage transition (ZVT) snubber cell is developed for pulse width modulated (PWM) and power factor corrected (PFC) boost converters operating in continuous conduction mode. A new family of PFC boost converter implemented with this new ZVT snubber cell is proposed. In this new PFC boost converter, the main switch is turned-on perfectly with ZVT and turned-off under zero-voltage switching (ZVS). Besides, the auxiliary switch is turned-on under zero current switching and turned-off under ZVS. The main and all auxiliary diodes are operating under soft switching. During ZVT operation, the switching energies on the snubber inductance are transferred to the output by a transformer, and so the current stresses of the inductance and the auxiliary switch are significantly decreased. Also, this transformer ensures the usage of sufficient capacitors for ZVS turning off of the main and auxiliary switches. The main switch and main diode are not subjected to any additional voltage and current stresses. In this study, a detailed steady-state analysis of the proposed new ZVT-PWM-PFC boost converter is presented and this theoretical analysis is verified by a prototype with 100 kHz and 2 kW.
Keywords: Boost converter; power factor correction (PFC); soft switching (SS); zero-voltage switching (ZVS); zero-voltage transition (ZVT); POWER-FACTOR CORRECTION; AC/DC CONVERTER; FLYBACK CONVERTER; BUCK CONVERTER; VOLTAGE; RECTIFIER; DESIGN; FAMILY; Automation & Control Systems; Engineering; Instruments & Instrumentation